CULTURAL METAMORPHOSIS: KAFKA AND THE THRESHOLDS OF EDITORIAL DESIGN - Seixas, Renato; Gárgoles Navas, María (Design/Arts/Culture, 2026)
In 2024, the centenary of Franz Kafka’s death inspired a collaborative academic project between the Universidad de Diseño, Innovación y Tecnología (UDIT, Madrid) and the Escola Superior de Artes e Design (ESAD, Porto). The initiative, entitled Kafka 2024, reinterpreted The Metamorphosis (1915) through editorial design as both a tribute to Kafka and a pedagogical experiment. The project was developed in five phases: an online workshop, a shared editorial briefing, six weeks of remote collaborative production, a public presentation at ESAD, and the final synthesis in a bilingual publication. This article analyzes the experience in relation to the theme “Polarities, Limits and Thresholds”. Results show that cultural and media polarities functioned as generative dialogues, institutional and temporal limits operated as catalysts for innovation, and pedagogical thresholds facilitated the transition from local classroom learning to international collaborative practice. Beyond the printed outcomes, the project fostered intercultural competencies, critical reflection on design processes, and reinforced institutional networks. The study demonstrates that editorial design can serve as a laboratory for applied research, capable of producing both creative artifacts and transferable pedagogical models. The collaboration between UDIT and ESAD illustrates how canonical literature can be reactivated as a framework for contemporary design education, where metamorphosis becomes a metaphor for learning in transition—from local to global, from theory to practice.